ENGLISH QUOTATIONS AND THEIR TRANSLATION INTO UZBEK: LINGUISTIC NATURE, CULTURAL CHALLENGES, AND TRANSLATION STRATEGIES - Amoniddinova Osiyo Toxirjon qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article explores the linguistic nature of quotations and their role as a specific type of “alien speech” within discourse, focusing on the challenges of translating English quotations into Uzbek. The research highlights the importance of cultural competence and pragmatic adequacy in achieving effective translation outcomes. Through illustrative examples, the paper demonstrates how dynamic equivalence ensures accurate meaning transfer across languages.